Empirical Model for Heat Transfer of Electric Submersible Pump (ESP) Motor at Oil Producer Well - Gunawan Gunawan; Idral Amri; Bahruddin Bahruddin (Journal of Earth Energy Engineering, 2019)
Motor operating temperature at wells equipped with Electric Submersible Pump (ESP) need to be monitored to maintain ESP performance run life. Not all producer wells equipped with temperature sensor, so it considered necessary to build mathematic model to estimate motor operating temperature. Model of heat transfer to predict motor operating temperature is developed based on empirical equation method. Parameter and variable data obtained from producer wells include water cut, viscosity, specific gravity, operating temperature, ampere and voltage. Procedure to calculate viscosity is ASTM D-88 and procedure to calculate specific gravity is ASTM D-5002. From 18 wells data obtained from the field, calculated reynolds numbers indicate turbulent flow regime with reynold numbers more than 4,000. Nusselt number were calculated using multiple linear regression with result of Nu = 0.06 * Re0.65 * Pr0.36 with error of 1.3% from downhole sensor measurement. The comparison with similar research also provided that use different Nusselt number empirical equation. The conclusion from the research showing that empirical approach by using specific constants to predict Nusselt number can be used to predict more accurate heat transfer coefficient with error 1.3%. Higher water cut fluid flow need lower fluid velocity to achieve motor operating temperature below motor limit temperature with fluid velocity above 0.3 m/s.